2019
DOI: 10.1371/journal.pone.0208958
|View full text |Cite
|
Sign up to set email alerts
|

Bioprinted liver provides early insight into the role of Kupffer cells in TGF-β1 and methotrexate-induced fibrogenesis

Abstract: Hepatic fibrosis develops from a series of complex interactions among resident and recruited cells making it a challenge to replicate using standard in vitro approaches. While studies have demonstrated the importance of macrophages in fibrogenesis, the role of Kupffer cells (KCs) in modulating the initial response remains elusive. Previous work demonstrated utility of 3D bioprinted liver to recapitulate basic fibrogenic features following treatment with fibrosis-associated agents. In the present study, culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 22 publications
1
56
0
Order By: Relevance
“…Furthermore, Organovo developed a bioprinting platform, in which, PHH, stellate cells, and KCs are bioprinted using nondisclosed bioink, where the cells showed five to ten times increased viability and albumin secretion compared to 2D culture after two weeks . Furthermore, the authors recently demonstrated that the model can recapitulate aspects of methotrexate‐induced fibrogenesis …”
Section: D Culture Paradigms For Phhmentioning
confidence: 99%
“…Furthermore, Organovo developed a bioprinting platform, in which, PHH, stellate cells, and KCs are bioprinted using nondisclosed bioink, where the cells showed five to ten times increased viability and albumin secretion compared to 2D culture after two weeks . Furthermore, the authors recently demonstrated that the model can recapitulate aspects of methotrexate‐induced fibrogenesis …”
Section: D Culture Paradigms For Phhmentioning
confidence: 99%
“…(17) Therefore, to date, most in vitro NAFLD studies involving PHHs have focused on short-term exposure (48-72 hours) to free fatty acids (FFAs), allowing the study of transient responses to triglyceride challenge. (14)(15)(16) Some studies using advanced in vitro platforms, including micropatterned co-cultures of primary hepatocytes and murine fibroblasts, (18) a hemodynamic co-culture system (19) or bioprinted cultures of primary liver cells, (20) have started to demonstrate how exposure to glucose and FFAs can affect human hepatic cell types. Moreover, with the addition of transforming growth factor β (TGF-β), early stages of fibrosis can be detected.…”
Section: A Microphysiological System For Studying Nonalcoholic Steatomentioning
confidence: 99%
“…Moreover, with the addition of transforming growth factor β (TGF-β), early stages of fibrosis can be detected. (20) We previously developed a model of hepatic steatosis using a 3D perfused microphysiological system (MPS), which enabled PHHs to be cultured for 2 weeks in the presence of FFAs, allowing the chronic effects of triglyceride accumulation to be analyzed. (21) The perfused MPS maintains highly metabolically active PHHs for extended periods (up to 40 days) (22)(23)(24) and has been demonstrated to support PHHs and human Kupffer cell (HK) co-cultures to study the effects of liver inflammation on drug metabolism, drug-drug interactions, and liver toxicity.…”
Section: A Microphysiological System For Studying Nonalcoholic Steatomentioning
confidence: 99%
“…These were cultured for several days and allowed to coalesce into liver tissue for studies of drug-induced toxicity. This same technique was also applied to the study of various compound-induced fibroses [93] and further explored by focusing on the role of Kupffer cells [94]. Ma et al [95] developed a 3D hydrogel-based hepatic bioprinting system using human iPSC stem cells to explore the liver tissue maturation process.…”
Section: Specialized Bioreactor Configurations (Sinusoid-like Structumentioning
confidence: 99%